Uma investigação da relação entre o Produto Interno Bruto (PIB), a inflação e o desemprego no Brasil (de 1999 a 2015) - Diogo Del Fiori; Salomão Franco Neves; Hecília Ricardo da Silva; Raphael Ribeiro Costa (Revista de Economia Mackenzie)
This monograph aimed to investigate the relation between Gross Domestic Product (GDP), inflation and unemployment in Brazil from 1999 to 2015. To achieve the objective, we used a descriptive methodology, ex post facto and quantitative method, using the linear regression model to investigate the relations along with the analysis of the average rate of change of the period. The conclusion reached is that through simple linear regression only the relation between unemployment rate and GDP (Okun Law) was proved, since the model generated for the relation between inflation and GDP and between unemployment and inflation did not yield solid results. Now, in the analysis of the average rate of variation showed that the behaviour of the variables as per the theory of Okun’s Law and Phillips Curve, while for inflation and GDP was found a direct relationship in the period.